Attentional Routes to Conscious Perception - Chica, Ana B.; Bartolomeo, Paolo (Frontiers in Psychology, 2012)
The relationships between spatial attention and conscious perception are currently the object of intense debate. Recent evidence of double dissociations between attention and consciousness cast doubt on the time-honored concept of attention as a gateway to consciousness. Here we review evidence from behavioural, neurophysiologic, neuropsychological and neuroimaging experiments, showing that distinct sorts of spatial attention can have different effects on visual conscious perception. While endogenous, or top-down attention, has weak influence on subsequent conscious perception of near-threshold stimuli, exogenous, or bottom-up forms of spatial attention appear instead to be a necessary, although not sufficient, step in the development of reportable visual experiences. Fronto-parietal networks important for spatial attention, with peculiar inter-hemispheric differences, constitute plausible neural substrates for the interactions between exogenous spatial attention and conscious perception.